Digital Governance: Biometric Registration and Privacy Challenges: the international and political journal - Al-Jubouri, Assist. Prof. Dr Ali Daryoul Mohammed (The International and Political Journal, 2025)
Objectives: Biometrics refers to the use of an individual’s unique biological characteristics, such as fingerprints, face, iris, or even voice, to identify an individual. Therefore, the study aims to review the most prominent contemporary technologies in the field of employing artificial intelligence in the field of biometric verification. Biometrics provides a powerful and effective means to enhance cybersecurity for countries by taking advantage of unique physiological and behavioral characteristics. Biometric verification provides enhanced security for the government database and an advanced technical experience for all its users. Methodology: The study follows the analytical approach that includes an explanation of the most prominent technical challenges associated with employing artificial intelligence technologies in the field of implementing (Biometric security) biometric security and biometric verification. Results: The results shows that implementing (Biometric security) biometric security requires careful study of appropriate methods, ensuring data security, integration with (Two-factor authentication for biometric verification), and regular system maintenance. In the overall evaluation, the results also shows that identification devices face recognition is highly demanded and recommended by the General Directorate of Narcotics Control